(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This study aimed to determine if developing a pedestrian bridge made of glulam wood from Makati to Mandaluyong is a good proposal. Thus, a survey was conducted to determine the structure of Glulam Bridge in terms of construction materials, design, feasibility, and presentation. This study was found acceptable by UP Architecture students and UP Civil Engineering students in terms of the cited variables. The two groups of respondents recommended using a concrete platform for the wooden bridge to allow the bridge to have a strong foundation and metal support for the bridge to make it heavier against water current. The respondents also recommended using a wood sealer to lessen the damage of water hitting on the wood. This study utilized quantitative research methods of the study. According to Farnsworth (2019), qualitative research is particularly suitable for exploratory research (e.g., during the pilot stage of a research project). It is primarily used to discover and gain an in-depth understanding of individual experiences, thoughts, opinions, and trends and to dig deeper into the problem at hand. The results of the study in terms of construction materials, design, feasibility, and presentation showed that the p-value for Architecture students was greater than the level of significance of 0.05 where the p-value was 0.70884, thereby showing a significant difference between the variable. The p-value of 0.80234 for Civil Engineering students was greater than the level of significance of 0.05, thereby showing a significant difference between the variables. The subsequent discussion forward by the two groups of respondents are as follows: select a more appropriate material for the bridge for safety purposes, use a concrete platform for the wooden bridge for a strong foundation, and use more beams to support the wooden bridge. Wood is an extremely expensive material; thus, use wood against water.